2019
DOI: 10.5578/ced.201922
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Diagnosis of Extrapulmonary Tuberculosis in Children

Abstract: Giriş: Tüberküloz (TB), hem gelişmekte olan hem de göç nedeniyle gelişmiş ülkelerde, kontrol stratejilerine rağmen insidansı artan önemli bir halk sağlığı sorunudur. Akciğer dışı tüberküloz (ADTB)'un klinik belirtilerinin çok farklı olması tanı ve tedavide gecikmelere neden olmaktadır. Çalışmamızda çocukluk yaş grubunda ADTB tanısı alan olguların klinik ve laboratuvar bulgularının değerlendirilmesi amaçlanmıştır. Gereç ve Yöntemler: Aralık 2007-Aralık 2017 tarihleri arasında fakültemiz çocuk enfeksiyon servisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…In this experiment, 92.8 percent of the total sputum samples showed positive results for pulmonary tuberculosis on a smear test; the fact that it poses a danger of infecting others by droplet or airborne transmission 16,17 is one reason why it could be considered a source of community contagiousness. In addition, the findings demonstrated that patients with EPTB were more likely to have pleural infections than any other type of infection, which is consistent with (9,18) in Iraq and (19,20) in Iran and Uzbekistan; further research has found that lymph nodes are to blame for nearly half of the cases of extra-pulmonary tuberculosis (EPTB) in Iraqi Kurdistan 21 and in Turkey 22 . For instance, the genitourinary system and the skin were the two most common sites of infection in Hong Kong 23 , but in the United States, bone and joint infections were more prevalent 24 .…”
Section: Discussionsupporting
confidence: 62%
“…In this experiment, 92.8 percent of the total sputum samples showed positive results for pulmonary tuberculosis on a smear test; the fact that it poses a danger of infecting others by droplet or airborne transmission 16,17 is one reason why it could be considered a source of community contagiousness. In addition, the findings demonstrated that patients with EPTB were more likely to have pleural infections than any other type of infection, which is consistent with (9,18) in Iraq and (19,20) in Iran and Uzbekistan; further research has found that lymph nodes are to blame for nearly half of the cases of extra-pulmonary tuberculosis (EPTB) in Iraqi Kurdistan 21 and in Turkey 22 . For instance, the genitourinary system and the skin were the two most common sites of infection in Hong Kong 23 , but in the United States, bone and joint infections were more prevalent 24 .…”
Section: Discussionsupporting
confidence: 62%
“…Other studies from the region also showed comparable results. Study done in Turkey reported it as 58.9% 15 , while in a study from Philippines it was positive in 87.9% patients. 20 In our study, the most affected age group was 5-10 years of age.…”
Section: Discussionmentioning
confidence: 88%
“…14 A Turkish study noted tuberculous lymphadenitis predominance in EPTB children (32%) followed by abdominal and TBM. 15 Another study from Ghana revealed disseminated TB as the commonest site 32.8% followed by pleural 18.4%. 16 So, all these studies show variation in terms of most frequent sties of EPTB and this is why it is vital to conduct studies among different populations for determination of most common sties of EPTB.…”
Section: Discussionmentioning
confidence: 95%
“…In our country, TST is used extensively in tuberculosis screening. However, TST can be affected by many factors such as BCG vaccine, immunity of the individual, application and interpretation technique of the screening tests (7) . IGRA has been used frequently in recent years, and its use is recommended in immunosuppressed patients with negative TST results or those using immunosuppressive drugs, and in TST-positive patients with poor prognosis but without any risk factor for tuberculosis disease to rule out false positivity (5) .…”
Section: Discussionmentioning
confidence: 99%